The role of social media in enhancing the modern market relations - Augustin Ignatov (CES Working Papers, 2019)
The Social media environment represents one of the most prospective domains of developing marketing campaigns. This fact is a result of the fundamental characteristics of social media networks which could be summarised by the following: low cost of developing an advertising campaign and a wide audience which it can be addressed to. The present research has found that social media marketing can provide immense opportunities in reaching target audiences. Social networks lead to the shrinking world phenomenon which is catalysed by the digital revolution. Moreover, the research has determined that social media changed the way people consume, thus clients are equally interested in the product itself as well as in the story standing behind this product. Communities created within social media platforms represent an important driver of local development. Social media acts as an intermediator between clients and firms increasing the quality of modern market relations since it provides the opportunity to maintain permanent feedback with all market participants. The general conclusion reached summarises the idea that business - consumer relations have been intensified due to the development of social media networks.
Keywords: M20; M30; O33; O35; P46; 330; democratisation of marketing; social networks; community relationship; Facebook; values sharing